Letter from Carl D. Duncan to Patricia Whiting, January 28, 1965 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Duncan recalls "My Fair Lady" and advises Whiting on how to respond to questions regarding his financial support of her.